A Comparative Life‐Cycle Assessment of Two Cogeneration Plants. Issue 11 (26th June 2019) - Siddiqui, Osamah; Dincer, Ibrahim
Abstract : Herein, a comparative energetic and life‐cycle assessment (LCA) study is performed on coal and natural gas‐based combined heat and power cogeneration plants. Different types of power plants, including gas turbine, steam turbine, and combined‐cycle plants, are considered. Three types of LCA methodologies, including CML 2001, TRACI, and ReCiPe, are used to analyze the life‐cycle environmental impacts of each plant. The coal‐based cogeneration plant is found to entail the comparatively lowest life‐cycle energy efficiency of 43.6%, and the natural gas‐based combined‐cycle cogeneration plant is found to have the highest efficiency of 59.6%. Furthermore, the coal‐based life cycle is also found to entail the highest life‐cycle environmental impacts comparatively. According to CML 2001, it entails a global‐warming potential of 0.229 kg CO2eq MJ −1 and an acidification potential of 7.03E‐4 kg SO2eq MJ −1 . The natural gas‐fired boiler‐type cogeneration plant is observed to have a comparatively higher toxicity and eutrophication potential of 2.72E‐4 kg DCBeq MJ −1 and 2.78E‐5 kg PO4eq MJ −1, respectively. The lowest overall life‐cycle environmental impacts comparatively are found to be associated with the natural gas‐based combined‐cycle cogeneration plant. Abstract : Herein, a comparative energetic and life‐cycle assessment study is performed on coal and natural gas‐based combined heat and power cogeneration plants. The coal‐based cogeneration plant is found to entail comparatively lowest life‐cycle energy efficiency and highest life‐cycle environmental impacts. However, cogeneration is found to improve the overall environmental performance of power plants.